EORTC Nomograms and Risk Groups for Predicting Recurrence, Progression, and Disease-specific and Overall Survival in Non-Muscle-invasive Stage Ta-T1 Urothelial Bladder Cancer Patients Treated with 1-3 Years of Maintenance Bacillus Calmette-Guerin - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
Background: There are no prognostic factor publications on stage Ta-T1 non-muscle-invasive bladder cancer (NMIBC) treated with 1-3 yr of maintenance bacillus Calmette-Guerin (BCG). Objective: To determine prognostic factors in NMIBC patients treated with 1-3 yr of BCG after transurethral resection of the bladder (TURB), to derive nomograms and risk groups, and to identify high-risk patients who should be considered for early cystectomy. Design, setting, and participants: Data for 1812 patients were merged from two European Organization for Research and Treatment of Cancer randomized phase 3 trials in intermediate- and high-risk NMIBC. Intervention: Patients received 1-3 yr of maintenance BCG after TURB and induction BCG. Outcome measurements and statistical analysis: Prognostic factors for risk of early recurrence and times to late recurrence, progression, and death were identified in a training data set using multivariable models and applied to a validation data set. Results and limitations: With a median follow-up of 7.4 yr, 762 patients recurred; 173 progressed; and 520 died, 83 due to bladder cancer (BCa). Statistically significant prognostic factors identified by multivariable analyses were prior recurrence rate and number of tumors for recurrence, and tumor stage and grade for progression and death due to BCa. T1G3 patients do poorly, with 1- and 5-yr disease-progression rates of 11.4% and 19.8%, respectively, and 1- and 5-yr disease-specific death rates of 4.8% and 11.3%. Limitations include lack of repeat transurethral resection in high-risk patients and exclusion of patients with carcinoma in situ. Conclusions: NMIBC patients treated with 1-3 yr of maintenance BCG have a heterogeneous prognosis. Patients at high risk of recurrence and/or progression do poorly on currently recommended maintenance schedules. Alternative treatments are urgently required. Patient summary: Non-muscle-invasive bladder cancer patients at high risk of recurrence and/or progression do poorly on currently recommended bacillus Calmette-Guerin maintenance schedules, and alternative treatments are urgently required. (C) 2015 European Association of Urology. Published by Elsevier B.V. All rights reserved.
Keywords: Non-muscle-invasive bladder cancer; Prognostic factors; Recurrence; Progression; Survival; Bacillus Calmette-Guerin; TRANSITIONAL-CELL CARCINOMA; PROGNOSTIC-FACTORS; FOLLOW-UP; TA; T1; IMMUNOTHERAPY; INSTILLATIONS; TABLES; MODEL